The Duties and Functions Performance of Aceh Human Resources Improvement Institutions in Scholarship Study Program Implementation in Aceh Government - Irfansyah (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The ability of employees in carrying out the duties and functions of LPSDM can be manifested if the employee has good work motivation, both physiologically, safety, appreciation, social, and self-actualization. the fact shows that LPSDM Aceh has not been able to carry out its duties and functions properly. On the other hand, LPSDM Aceh has not been able to transparently select scholarship recipients. This happens because there are still many recipients of entrusted scholarships from the Aceh government, so that the LPSDM does not appear to be independent in distributing scholarships. The formulation of this thesis problem is How the tasks and functions of the Aceh Human Resources Improvement Institution (LPSDM) in the implementation of further study scholarship programs in Aceh Government and how the performance of employees of the Aceh Human Resources Development Agency (LPSDM) in implementing the scholarship program at the Aceh Government. The purpose of this research is to find out and analyze the tasks and functions of the Aceh Human Resources Improvement Institution (LPSDM) in the implementation of further study scholarship programs in Aceh Government and to find out and analyze the performance of Aceh Human Resources Development Agency (LPSDM) employees in implementing the scholarship program at the Aceh Government. This study uses a qualitative approach with as many as 5 people informants consisting of thus the research assign research informants as many as 4 people consisting of the Head of the LPSDM Secretariat, Sub Division of Finance, Planning and Treasurer Routine. Data collection is done by using observation, interview and documentation techniques. The results of the study prove that the duties and functions as well as the performance of LPSDM Aceh in the implementation of further study scholarship programs in Aceh Government have not been carried out in accordance with Aceh's Governor Regulation No. 11 of 2016 concerning LPSDM Aceh. Thus it can be concluded that the duties and functions of the Aceh Human Resources Improvement Institution (LPSDM) as the implementer of the advanced study scholarship program at Aceh Government can be seen the speed of access, so as to have equal rights between various groups.